Beta-boswellic acid facilitates diabetic wound healing by targeting STAT3 and inhibiting ferroptosis in fibroblasts - Ziyang Han; Weiping Wu; Zeming Bai; Yiping Xiu; Dapeng Zhou (Frontiers in Pharmacology)
ObjectiveDiabetic wounds are a severe complication of diabetes, with persistently high incidence and mortality rates, often leading to severe clinical outcomes such as amputation. Beta-boswellic acid (β-BA) is a plant-derived pentacyclic triterpene with activities of inflammatory control and ferroptosis regulation. However, the protective effect of β-BA on DW has not been described.MethodWe employed network analysis approaches and molecular docking to predict the potential targets and pathways of β-BA in the treatment of diabetic wounds (DW). Both in vitro and in vivo models were established, including high-glucose-induced fibroblast models and diabetic rat wound models. The effects of β-BA on diabetic wounds were investigated through CCK-8 assay, wound healing assay, immunofluorescence staining, western blotting, fluorescent probe analysis, gross observation, and histopathological experiments.ResultIn this study, we predicted potential targets for β-BA using public databases and identified 29 key genes, with STAT3 being the most significant. GO analysis revealed that these targets are involved in biological processes closely related to ferroptosis, such as regulation of inflammatory response and lipid metabolism. Our results showed that HG induced ferroptosis in HSFs, as evidenced by decreased cell viability, altered GSH/MDA, Fe2+, and ROS levels, and changes in the expression of ferroptosis-related genes ACSL4 and GPX4. Notably, treatment with the ferroptosis inhibitor Ferr-1 partly reversed these effects. CCK-8 assays showed that β-BA improved HSFs viability in a concentration-dependent manner. Immunofluoresc-ence staining and further biochemical analyses demonstrated that β-BA reduced Fe2+ and lipid peroxide levels, prevented oxidative damage, and improved cell migration ability impaired by HG. Western blot analysis confirmed that β-BA reversed the changes in ACSL4 and GPX4 expression induced by HG. Molecular docking validated the potential binding between β-BA and STAT3. Western blot analysis revealed that β-BA increased the level of phosphorylated STAT3 in HSFs. Introducing a STAT3 inhibitor diminished the beneficial effects of β-BA on HG-induced cell dysfunction and suppressed its protective effect against ferroptosis. Finally, we assessed the efficacy of β-BA in the treatment of diabetic wounds in rats. BA administration accelerated wound closure, reduced inflammatory cell infiltration, improved granulation tissue arrangement, and increased collagen deposition. Immunohistochemical staining showed that BA upregulated the number of STAT3-positive cells and upregulated the number of GPX4-positive cells in the wounds, suggesting that BA can inhibit ferroptosis and accelerate wound healing in diabetic rats.ConclusionOur findings suggested that β-BA may exert its therapeutic effects on diabetic wounds by targeting STAT3 and inhibiting ferroptosis.